2022
DOI: 10.1001/jama.2022.10018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Testing for Next-Step Antidepressant Selection

Abstract: Among patients with major depressive disorder (MDD), less than 40% achieve clinical remission after an initial treatment with an antidepressant. For those who do not improve after 2 or more antidepressant treatment trials (ie, treatment-resistant depression), the rates of remission are less than 20%. 1 Because each of these failed treatments translates to several months of prolonged illness, a series of multiple ineffective treatments contributes to the substantial disability and morbidity associated with MDD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Over the years, several reasons have been proposed to explain this phenomenon. Among them, there are a relative lack of RCTs exploring PGx efficacy [11], a lack of knowledge on how to interpret its results by a sizeable portion of healthcare providers [11], inconsistencies in the guidance provided by different clinical practice guidelines [23], and an apparent lack of confidence in the overall value of PGx testing in clinical practice [11,81]. The results of our review seem to point to a significant heterogeneity in assessed outcomes and in the testing panels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Over the years, several reasons have been proposed to explain this phenomenon. Among them, there are a relative lack of RCTs exploring PGx efficacy [11], a lack of knowledge on how to interpret its results by a sizeable portion of healthcare providers [11], inconsistencies in the guidance provided by different clinical practice guidelines [23], and an apparent lack of confidence in the overall value of PGx testing in clinical practice [11,81]. The results of our review seem to point to a significant heterogeneity in assessed outcomes and in the testing panels.…”
Section: Discussionmentioning
confidence: 92%
“…These factors, taken together, may increase PGx adoption in clinical practice [23]. Future efforts need to be devoted to improving the standardization for the tested algorithms and clinical practice guidelines, boosting educational programs on how to capitalize on PGx technologies in clinical care and assessing next-generation sequencing in PGx tests to address some of the lasting concerns surrounding PGx use [11,81,87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies 39 , 40 , 41 , 42 of treatment for MDD guided by pharmacogenetics examined the use of combinatorial pharmacogenetic tests (ie, multigene testing). Other studies 14 , 43 , 44 , 45 found promising results regarding remission rates; however, questions have been raised about whether the studies were properly randomized and blinded. 43 In most previous studies, 39 , 40 , 41 , 42 information was not presented regarding how the pharmacogenetic test results were translated into the choice for a specific antidepressant or antidepressant dosage as well as the extent to which the prescribers adhered to the dosing advice in their treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 In the Precision Medicine in Mental Health Care randomized clinical trial (NCT03170362), pharmacogenomic testing reduced prescription of medications associated with drug‐gene interactions but had only a small and nonpersistent effect on symptom remission 17 . Pharmacogenomics may identify variants that predict pharmacokinetic interactions as well as pharmacodynamic actions 49,50 . Future studies of patients with DGBI should compare therapy guided by pharmacogenomic testing with the standard of care to assess the extent to which pharmacogenomic testing guides prescriber patterns and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%